USE OF ENVIRONMENTALLY FRIENDLY FISHING GEAR FOR SUSTAINABLE TRADITIONAL FISHERMEN'S INCOME - Faisal Matriadi; Saifuddin; Mariyudi; Ikramuddin; Em Yusuf Iis; A Hadi Arifin; Chalirafi; Ristati; Wahyuddin Albra (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Poverty is a fundamental problem that still surrounds some of the people of Ulee Jalan Village, Banda Sakti District, Lhokseumawe City. Poverty is a condition of lack of income that causes a low quality of life. Based on existing data, poverty has also caused worrying juvenile delinquency behavior and parenting patterns that are not as expected. Another finding in Ulee Jalan Village is that there is a significant number of stunted babies, reaching 21 people in 2023. Based on the initial needs assessment from the interview results, there is a problem that many people still have low incomes and are economically powerless and they do not understand how to get out of poverty by using MSMEs, then the role of the family as the first educational institution has not been fully obtained by some teenagers in Ulee Jalan Village. The influence of inappropriate parenting patterns forms bad character in teenagers, as well as adolescent social patterns that are not controlled by parents. The emergence of criminal cases with children and adolescents as subjects or objects does require special study. This concern needs to be investigated, what is actually the background of the problem, how is its dynamics and what efforts can be used as a solution and anticipation so that the problem does not spread. Furthermore, poor understanding of nutrition and minimal income have an impact on the high rate of stunting, one of the causes of which is poverty. The specific objectives are: 1) Providing information related to innovation and creativity that can be done to increase income so that MSME actors can increase their business productivity, 2) Providing assistance and empowerment of MSME actors in business development, and 3) Providing an understanding to mothers and young women about the importance of the role of parents in educating children and creating a happy family to support the formation of quality adolescent characters, 4) Providing an understanding of the causes of stunting in infants and how to overcome it, especially strategies for providing sufficient nutritional intake for infants from infancy to the first 1000 days of life. The location of community service is determined at Ulee Jalan, Banda Sakti District, Lhokseumawe City. This is because the location of this area is an area that has problems related to adolescent rights, so it is hoped that this service can provide a direct contribution to solving problems faced by poor communities and MSME actors and also solving juvenile delinquency and stunting issues. This training activity was carried out for two days on Saturday-Sunday, August 24-25, 2024 starting from 08.00 am to 18.00 pm or for 18 effective hours. The method used is Collaborative Decision Making: Community-Based Methods with the SARAR approach. This participatory approach is specifically intended for training local trainers/facilitators, building local knowledge and strengthening local capacity to assess, prioritize, plan, create,organize, and evaluate. Workshops and mentoring to increase understanding of the importance of the role of the family in the formation and development of the character of adolescents and parents and efforts to reduce stunting. The fundamental contribution to a field of science is to contribute to the development of science, especially by enriching the treasury of theories and concepts as well as models for Empowering MSME Actors and parenting patterns that reduce juvenile delinquency and significantly reduce stunting rates.